The reward‐like nature of social cues that indicate successful altruistic punishment. (27th April 2018) - Mussel, Patrick; Hewig, Johannes; Weiß, Martin
Abstract: Altruistic punishment is the attempt to penalize deviant behavior of another person even though it is accompanied by personal costs. Here, we investigated the influence of the reaction on the socioemotional level of the other person following altruistic punishment behavior on future decision making and neural responses. We used a modified ultimatum game, which included an emotional facial feedback of the proposer following the decision of the participant. We found higher acceptance rates for proposers showing a smile upon acceptance or a sad face upon rejection of an offer, compared to proposers showing a neutral facial expression. On the neural level, we found a reversed N2 effect for negative emotional faces in the context of altruistic punishment, compared to a control condition. Specifically, when following the rejection of an unfair offer, negative emotional faces showed a reward‐like positivity that might signal successful altruistic punishment. In addition, differential effects for P3 amplitudes might signal the subjective importance of a desired outcome. Our results are in line with the interpretation that rejection of unfair offers in the ultimatum game is due to intended altruistic punishment. Social cues may exhibit reward‐like properties when indicating successful altruistic punishment and can influence subsequent decision making.